Intronic sequences and 3' splice sites control Rous sarcoma virus RNA splicing. - McNally, M T (1992)
cis-acting sequences of Rous sarcoma virus (RSV) RNA involved in control of the incomplete splicing that is part of the retroviral life cycle have been studied. The 5' and two alternative 3' splice sites, as well as negative regulator of splicing element in the intron, have been introduced into chimeric constructs, and their responsive roles in splicing inhibition have been evaluated by transient transfection experiments. Although the RSV 5' splice site was used efficiently in these assays, substrates containing either the RSV env or the RSV src 3' splice site were not spliced completely, resulting in 40 to 50% unspliced RNA. Addition of the negative regulator of splicing element to substrates containing RSV 3' splice sites resulted in greater inhibition of splicing (70 to 80% unspliced RNA), suggesting that the two elements function independently and additively. Deletion of sequences more than 70 nucleotides upstream of the src 3' splice site resulted in efficient splicing at this site, suggesting that inefficient usage is not inherent in this splice site but is instead due to to sequences upstream of it. Insertion of these upstream sequences into the intron of a heterologous pre-mRNA resulted in partial inhibition of its splicing. In addition, secondary structure interactions were predicted to occur between the src 3' splice site and the inhibitory sequences upstream of it. Thus, RSV splicing control involves both intronic sequences and 3' splice sites, with different mechanisms involved in the underutilization of the env and src splice acceptor sites.